Ibn Al-Arabi on Fundamental Religious Notions: Natural Disposition (Fitrah), Divine Law (Shar’), True Faith (Iman) and Disbelief (Kufr) - bin Badron, Mohd Sani (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Ibn Al-Arabi on Fundamental Religious Notions: Natural Disposition (Fitrah), Divine Law (Shar’), True Faith (Iman) and Disbelief (Kufr)